Technical outcomes and postprocedural courses of mucosal incision‐assisted biopsy for possible gastric gastrointestinal stromal tumors: A series of 48 cases (with video) - Eriko Koizumi; Osamu Goto; Shun Nakagome; Tsugumi Habu; Yumiko Ishikawa; Kumiko Kirita; Hiroto Noda; Kazutoshi Higuchi; Takeshi Onda; Teppei Akimoto; Jun Omori; Naohiko Akimoto; et al. (DEN Open)
Abstract Objective Mucosal incision‐assisted biopsy (MIAB) has been introduced as an alternative to endoscopic ultrasound‐guided fine needle aspiration for tissue sampling of subepithelial lesions. However, there have been few reports on MIAB, and the evidence is lacking, particularly in small lesions. In this case series, we investigated the technical outcomes and postprocedural influences of MIAB for gastric subepithelial lesions 10 mm or greater in size. Methods We retrospectively reviewed cases with the intraluminal growth type of possible gastrointestinal stromal tumors, in which MIAB was performed at a single institution between October 2020 and August 2022. Technical success, adverse events, and clinical courses following the procedure were evaluated. Results In 48 MIAB cases with a median tumor diameter of 16 mm, the success rate of tissue sampling and the diagnostic rate were 96% and 92%, respectively. Two biopsies were considered sufficient for making the definitive diagnosis. Postoperative bleeding occurred in one case (2%). In 24 cases, surgery has performed a median of two months after MIAB, and no unfavorable findings caused by MIAB were seen intraoperatively. Finally, 23 cases were histologically diagnosed as gastrointestinal stromal tumors, and no patients who underwent MIAB experienced recurrence or metastasis during a median observation period of 13 months. Conclusions The data indicated that MIAB appears feasible, safe, and useful for histological diagnosis of gastric intraluminal growth types of possible gastrointestinal stromal tumors, even those of a small size. Postprocedural clinical effects were considered negligible.